Research on the Training of Talents in Economic and Management in New Business Forms - Wang, Dong (Transactions on Economics, Business and Management Research, 2024)
In today’s rapidly evolving new business forms, higher demands are placed on both the professional capabilities and comprehensive qualities of talents. Therefore, universities must keep pace with the times in training talents in economic and management, ensuring that the cultivated talents meet the needs of societal development. To this end, universities should closely monitor industry trends, understand the development trends of new business forms and changes in talent demands, and accordingly adjust and optimize the curriculum to ensure that course content is closely linked to social needs. Furthermore, universities should strengthen practical teaching segments, providing students with more opportunities to engage with real work environments through collaborations with enterprises and practical training. This enables students to learn and grow in practice, enhancing their hands-on and problem-solving skills. Lastly, universities should also focus on cultivating students’ overall qualities and innovative abilities. By offering interdisciplinary courses and organizing innovative practice activities, they can stimulate students’ innovative thinking and entrepreneurial spirit, fostering their critical thinking, teamwork, and effective communication skills to meet the needs of national development and social progress.